2021
DOI: 10.1002/casp.2570
|View full text |Cite
|
Sign up to set email alerts
|

Multiple group membership supports resilience and growth in response to violence and abuse

Abstract: This paper examines the role that social group processes, and multiple group membership in particular, play in supporting resilience and post-traumatic growth following the experience of violence and abuse. Drawing on social identity theorizing, we develop and test a model that (a) predicts an association between multiple group membership and positive outcomes of resilience and post-traumatic growth, and (b) explores mechanisms, of personal control and identification with anti-violence activists, through which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The main topics encompassed here are the effects of being part of multiple social groups on individuals' (mental) health and well-being (e.g., Bule and Frings, 2015;Kinsella et al, 2020;Gallagher et al, 2021;Rees et al, 2022) or cognitive processing and performance (e.g., Woods et al, 2018;Beadleston et al, 2019). Furthermore, it also covers multiple group membership in relation to other social psychology themes, such as self-esteem (Jetten et al, 2015), aging (Ysseldyk et al, 2013), divorce (Lampraki et al, 2019), resilience in violence and abuse (Haslam et al, 2022), and protest (Besta et al, 2019). This cluster did not emerge in the first citation analysis, very likely due to the fact that the papers included in this cluster do not connect well with the other papers from the other clusters and hence were excluded from the sample used for the network.…”
Section: Study Citation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The main topics encompassed here are the effects of being part of multiple social groups on individuals' (mental) health and well-being (e.g., Bule and Frings, 2015;Kinsella et al, 2020;Gallagher et al, 2021;Rees et al, 2022) or cognitive processing and performance (e.g., Woods et al, 2018;Beadleston et al, 2019). Furthermore, it also covers multiple group membership in relation to other social psychology themes, such as self-esteem (Jetten et al, 2015), aging (Ysseldyk et al, 2013), divorce (Lampraki et al, 2019), resilience in violence and abuse (Haslam et al, 2022), and protest (Besta et al, 2019). This cluster did not emerge in the first citation analysis, very likely due to the fact that the papers included in this cluster do not connect well with the other papers from the other clusters and hence were excluded from the sample used for the network.…”
Section: Study Citation Analysismentioning
confidence: 99%
“…The most frequently used keyword is "multiple group membership", which represents the extent to which an individual is part of multiple social groups (e.g., community groups; sports groups) (Gallagher et al, 2021). The Social Identity Theory (Tajfel and Turner, 1979;Tajfel, 1982) and also Self-Categorization Theory (Turner et al, 1987) that explain how membership in various social groups (family, community, religious, sporting) shape social identity or the way in which we develop our sense of self and we derive self-esteem from these memberships (Haslam et al, 2022). Multiple group membership benefits the health and well-being of individuals because they have access to multiple social identities that keep them connected to other people, provide structure and meaning to social relationships (Greenaway et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Indeed, women who have experienced GBD report greater awareness of its prevalence and increased desire to help other survivors (Valentine et al, 2017). Additionally, researchers have found that identifying as an activist is associated with greater post-traumatic growth following experiences of GBD (C. Haslam et al, 2021), which suggests that emphasising collective action norms in response to victimisation may facilitate trajectories of growth. A clear direction for future research would therefore be to consider the effect of historical sexual victimisation on appraisal of present or hypothetical GBD.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we see this as evidence for a broader 'social cure' (cf. C. Haslam et al, 2018): closely held and salient social identities provide a sense of agency and facilitate collective action (Greenaway et al, 2015;C. Haslam et al, 2021).…”
Section: Np22936mentioning
confidence: 99%
“…A growing body of research shows group memberships can drive personal PTG (Griffin et al., 2022; Muldoon et al., 2017). In women who have experienced gender‐based violence in South Africa, for example, positive responses (including PTG) were facilitated by prior group membership, which acted as a platform for enhanced feelings of personal control and identification (Haslam et al., 2022). These findings are consistent with previous work that demonstrated involvement in anti‐sexual assault activism promoted PTG (Strauss Swanson & Szymanski, 2020).…”
Section: Introductionmentioning
confidence: 99%